DESAIN KELEMBAGAAN DALAM KOLABORASI PENCEGAHAN KEMATIAN IBU SAAT PERSALINAN - Rininta Andriani; La Ode Syaiful Islamy (J-KESMAS: Jurnal Kesehatan Masyarakat, 2020)
Efforts to prevent maternal death during childbirth have become a serious concern of the government and society. Many factors cause maternal death; one of the factors is the lack of access to good services for maternal health, especially the punctuality of emergencies caused by being late in making decisions to get treatment, the second is late arriving at health facilities, and the third is late in getting adequate and appropriate treatment. The efforts to prevent maternal death during childbirth can be made by collaborating to design institution collaborative of maternal death prevention at first. The purpose of this research was to describe the collaborative institution design of maternal death prevention during childbirth in South Buton Regency using a qualitative method with a phenomenological approach, data collected through observation, interviews, and document study and analyzed with the stages of data reduction, data display, and conclusion drawing/verification. The result showed that in designing the institution, this could be seen from society's large participation based on equality and sharing of understanding from the collaborative actors. The establishment of a limited forum resulted from discussions carried out, which was legitimated in terms of basic rules of collaboration supporter that combined between customary regulations and customs of ancestors and applicable statutory regulations.